PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR PPKn SISWA KELAS IV MI AL BASIRAH KOTA MAKASSAR - Yusmarani; Faisal , Muhammad; Pada , Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is an experimental research aimed at determining the effect of the use of the Think Pair Share cooperative learning model and flashcard media on the Civics (PPKn) learning outcomes of fourth grade students at MIS Al Bashirah. The approach used in this research is a quantitative approach with an experimental research type. This study applies a quasi-experimental research design in the form of a non-equivalent control group design. The research data were obtained through observation sheets and tests. The population in this study consisted of all students of MIS Al Bashirah totaling 54 students. The sample in this study was the fourth grade students of MIS Al Bashirah, totaling 54 students, divided into two classes: class IVC with 26 students and class IVD with 28 students. The data analysis techniques used were descriptive and inferential statistical analysis. The results of this study indicate that: (1) The implementation of the Think Pair Share learning model in fourth grade students at MIS Al Bashirah, Makassar City is categorized as very good. (2) The use of flashcard media among fourth grade students at MIS Al Bashirah, Makassar City is categorized as very good. (3) The Civics (PPKn) learning outcomes of fourth grade students at MIS Al Bashirah are higher in the experimental class compared to the control class, while the control class learning outcomes are still in the sufficient category and not yet optimal. (4) There is a significant effect of the Think Pair Share cooperative learning model and flashcard media on the Civics (PPKn) learning outcomes of fourth grade students at MIS Al Bashirah, Makassar City.